Analysis of Financial and Non-Financial Performance of Marine Capture Fisheries Using Gillnet in Pulau Baai Port of Bengkulu Province - Tambunan, Yohana; Sukiyono, Ketut; Romdhon, Mustopa (Indonesian Journal of Agricultural Research, 2018)
This study is aimed at analyzing the financial and non-financial performance of marine capture fisheries business in Baai Island Port. Stratified random sampling including 60 fishermen using gillnet fishing gear in Baai Island Port was used in this survey. The method used both financial performance including the analysis of income, B/C, Break Even Point (BEP), and non-financial performance including the analysis of the productivity of fishing gear, fishermen and fishing trip. The analysis showed that the income of fishermen in Baii Island was IDR 1,880,545 per trip, the B/C was 0.25, the BEP (unit) was 322 kg, and the productivity of fishing gear was 8 kg per unit, the fishermen productivity was 72 kg per person and the catching productivity was 30 kg per trip